Action Research Proposal Preparation Workshop Class (CAR) for the Indonesian Social Sciences Teacher Forum (Fogipsi) West Kalimantan Region - Haris Firmansyah; Hadi Wiyono; Iwan Ramadhan; Shilmy Purnama; Nur Meily Adlika; Jumardi Budiman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Classroom Action Research (CAR) is a type of research that is considered the most appropriate for teachers, besides being able to improve learning which will have an impact on the quality of education. The objectives of the CAR implementation and report preparation training activities are as follows: (1) Improving teachers' understanding of the CAR implementation procedures; (2) Improving the skills of teachers to carry out CAR; (3) Improving teacher skills in writing CAR reports; (4) Increase the quantity of teacher publications in periodic scientific journals. The community that is the target of this PKM activity is the 16 teachers at FOGIPSI, the teachers who become participants are determined based on their interest in improving CAR skills. The steps for the realization of the PKM problem solving phase are as follows: (1) Conducting a workshop on the correct CAR concepts and procedures according to scientific principles. The presenters of the workshop are members of the research TEAM. (2) Forming a working group consisting of 5 teachers per group. Group members attempted to be heterogeneous in terms of gender, level of education and the value of a previously distributed questionnaire. And (3) Assist the group in preparing the CAR proposal.